Analysis of an alternative method for the study of bromeliad-associated fauna in plants with different foliar organization - Müller,Gerson A. (2010)
The efficiency of an alternative method of collection (by suction of water) for the study of Culicidae and Chironomidae (Diptera), Scirtidae (Coleoptera) and Coenagrionidae (Odonata) in bromeliads with different foliar architecture in a restinga at Florianópolis, SC, Brazil, was studied. The alternative method was less efficient to collect Culicidae and Chironomidae (Wilcoxon test p < 0.05) and was more efficient to Scirtidae and Coenagrionidae (Wilcoxon test p > 0.05) from Aechmea lindenii. This method was less efficient to collect insects of all groups from Vriesea friburgensis (Wilcoxon test p < 0.05). The alternative method was efficient to estimate the diversity of these insects in both species of bromeliads. The higher mobility of immature forms of beetles and dragonflies, and the availability of only one tank in Aechea lindenii, contrasting to several tanks in Vriesea friburgensis that help the suction of these immature, probably influenced the results, which indicated that the suction method should not replace the dismantling in the study of Culicidae and Chironomidae. This method can be useful to get immature forms of Scirtidae and Coenagrionidae in one-tank bromeliads.